PENGARUH HASIL BELAJAR PENGANTAR ILMU EKONOMI TERHADAP GAYA HIDUP MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Uba, Rn Abu Darda; Syahrudin, Husni; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of learning outcomes introduction to behavioral economics Economy Education Student Guidance and Life Style Tanjungpura University's Pontianak. The research method used is associative research methods and forms of survey research. The population consists of 279 students and the sample totaled 74 students. Test results hypothesis testing with simple regression coefficients (t test) that there are significant   learning   outcomes   introduction   to   behavioral   economics Economy Education Student Guidance and Counseling consumption Tanjungpura University's Pontianak with value t count < t table (0.660 <1.994),   then   H0     accepted   and   Ha   is   rejected,   the   Coefficient   of Determination Test (R2) that, learning outcomes introductory economics life syle of Economics Faculty of Teacher Education students Tanjungpura University's Pontianak by 0,6%. Keywords: Learning Outcomes, Introduction to Economics, Life Style